Well-posedness characterizations for system of mixed hemivariational inequalities - Kartikeswar Mahalik; Chandal Nahak (Miskolc Mathematical Notes)
In this paper, we concern with the concept of well-posedness and well-posedness in generalized sense for a system of mixed hemivariational inequality (SMHVI) with perturbations. We establish several metric characterizations and equivalent conditions of well-posedness for SMHVI. Our main results improve and extend some announced work in the literature.